EAT-Lancet diet and risk of metabolic dysfunction-associated steatotic liver disease and other liver chronic diseases: a large prospective cohort study in the UK Biobank - Wu, Shi-Yi; Bo, Ya-Cong; Li, Ze-Yang; Hu, Xing-Yue; Ning, Yang-Yang; Huang, Jia; Zhang, Jun-Xi; Zhu, Yong-Jian; Yu, Zeng-Li; Liu, Hong-Yan (Frontiers in Nutrition, 2025)
Background and aimAs a newly recommended healthy dietary blueprint, the EAT-Lancet diet emphasizes both environmental sustainability and human health. However, its impact on chronic liver diseases remains unclear. This study examined the influence of the EAT-Lancet diet on the risk of metabolic dysfunction-associated steatotic liver disease (MASLD) and other chronic liver diseases.MethodsOur study included 160,394 UK Biobank participants who completed 24-h dietary assessments between April 2009 and June 2012, from which EAT-Lancet diet scores were calculated. The Cox proportional hazards models were used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs) for the primary outcome (MASLD) and secondary endpoints, including cirrhosis, liver cancer, and other liver diseases.ResultsA total of 1,727 cases of MASLD, 602 cases of liver cirrhosis, 103 cases of liver cancer, and 2,053 cases of other liver diseases were identified over a median follow-up period of 13.3 years. Using the lowest tertile as the reference, the highest EAT-Lancet diet index group demonstrated a 33% reduction in MASLD incidence (HR:0.67, multivariate 95%CI: 0.55, 0.80). In several secondary outcome measures, similar associations were also observed. Furthermore, the risk of MASLD was lowest among individuals with both higher EAT-Lancet dietary scores and lower genetic risk (HR = 0.52; 95%CI: 0.36–0.74), although no significant interaction was detected between the two groups.ConclusionAdherence to the EAT-Lancet diet is associated with a reduced risk of chronic liver disease, independent of genetic factors.